Numerical investigation of a small footprint plasmonic Bragg grating structure with a high extinction ratio - Butt, Muhammad Ali (Photonics Letters of Poland, 2020)
In this paper, miniaturized design of a plasmonic Bragg grating filter is investigated via the finite element method (FEM). The filter is based on a plasmonic metal-insulator-metal waveguide deposited on a quartz substrate. The corrugated Bragg grating designed for near-infrared wavelength range is structured on both sides of the waveguide. The spectral characteristics of the filter are studied by varying the geometric parameters of the filter design. As a result, the maximum ER and bandwidth of 36.2 dB and 173 nm is obtained at λBragg=976 nm with a filter footprint of as small as 1.0 x 8.75 µm2, respectively. The ER and bandwidth can be further improved by increasing the number of grating periods and the strength of the grating, respectively. Moreover, the Bragg grating structure is quite receptive to the refractive index of the medium. These features allow the employment of materials such as polymers in the metal-insulator-metal waveguide which can be externally tuned or it can be used for refractive index sensing applications. The sensitivity of the proposed Bragg grating structure can offer a sensitivity of 950 nm/RIU. We believe that the study presented in this paper provides a guideline for the realization of small footprint plasmonic Bragg grating structures which can be employed in filter and refractive index sensing applications. Full Text: PDF References J. W. Field et al., "Miniaturised, Planar, Integrated Bragg Grating Spectrometer", 2019 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference (CLEO/Europe-EQEC), Munich, Germany, 2019, CrossRef L. Cheng, S. Mao, Z. Li, Y. Han, H.Y. Fu, "Grating Couplers on Silicon Photonics: Design Principles, Emerging Trends and Practical Issues", Micromachines, 11, 666 (2020). CrossRef J. Missinne, N. T. Beneitez, M-A. Mattelin, A. Lamberti, G. Luyckx, W. V. Paepegem, G. V. Steenberge, "Bragg-Grating-Based Photonic Strain and Temperature Sensor Foils Realized Using Imprinting and Operating at Very Near Infrared Wavelengths", Sensors, 18, 2717 (2018). CrossRef M. A. Butt, S.N. Khonina, N.L. Kazanskiy, "Numerical analysis of a miniaturized design of a Fabry–Perot resonator based on silicon strip and slot waveguides for bio-sensing applications", Journal of Modern Optics, 66, 1172-1178 (2019). CrossRef H. Qiu, J. Jiang, P. Yu, T. Dai, J. Yang, H. Yu, X. Jiang, "Silicon band-rejection and band-pass filter based on asymmetric Bragg sidewall gratings in a multimode waveguide", Optics Letters, 41, 2450 (2016). CrossRef M. A. Butt, S.N. Khonina, N.L. Kazanskiy, "Optical elements based on silicon photonics", Computer Optics, 43, 1079-1083 (2019). CrossRef N. L. Kazanskiy, S.N. Khonina, M.A. Butt, "Plasmonic sensors based on Metal-insulator-metal waveguides for refractive index sensing applications: A brief review", Physica E, 117, 113798 (2020). CrossRef L. Lu et al, "Mode-Selective Hybrid Plasmonic Bragg Grating Reflector", IEEE Photonics Technology Letters, 22, 1765-1767 (2012). CrossRef R. Negahdari, E. Rafiee, F. Emami, "Design and simulation of a novel nano-plasmonic split-ring resonator filter", Journal of Electromagnetic Waves and Applications, 32, 1925-1938 (2018). CrossRef M. Janfaza, M. A. Mansouri-Birjandi, "Tunable plasmonic band-pass filter based on Fabry–Perot graphene nanoribbons", Applied Physics B, 123, 262 (2017). CrossRef C. Wu, G. Song, L. Yu, J.H. Xiao, "Tunable narrow band filter based on a surface plasmon polaritons Bragg grating with a metal–insulator–metal waveguide", Journal of Modern Optics, 60, 1217-1222 (2013). CrossRef J. Zhu, G. Wang, "Sense high refractive index sensitivity with bragg grating and MIM nanocavity", Results in Physics, 15, 102763 (2019). CrossRef Y. Binfeng, H. Guohua, C. Yiping, "Design of a compact and high sensitive refractive index sensor base on metal-insulator-metal plasmonic Bragg grating", Optics Express, 22, 28662-28670 (2014). CrossRef A.D. Simard, Y. Painchaud, S. Larochelle, "Small-footprint integrated Bragg gratings in SOI spiral waveguides", International Quantum Electronics Conference Lasers and Electro-Optics Europe, IEEE, Munich, Germany (2013). CrossRef C. Klitis, G. Cantarella, M. J. Strain, M. Sorel, "High-extinction-ratio TE/TM selective Bragg grating filters on silicon-on-insulator", Optics Letters, 42, 3040 (2017). CrossRef J. Ctyroky et al., "Design of narrowband Bragg spectral filters in subwavelength grating metamaterial waveguides", Optics Express, 26, 179 (2018). CrossRef M.A. Butt, N.L. Kazanskiy, S.N. Khonina, "Hybrid plasmonic waveguide race-track µ-ring resonator: Analysis of dielectric and hybrid mode for refractive index sensing applications", Laser Phys., 30, 016202 (2020). CrossRef M. A. Butt, N.L. Kazanskiy, S.N. Khonina, "Label-free detection of ambient refractive index based on plasmonic Bragg gratings embedded resonator cavity sensor", Journal of Modern Optics, 66, 1920-1925 (2019). CrossRef N. L. Kazanskiy, M.A. Butt, Photonics Letters of Poland, 12, 1-3 (2020). CrossRef Z. Guo, K. Wen, Q. Hu, W. Lai, J. Lin, Y. Fang, "Plasmonic Multichannel Refractive Index Sensor Based on Subwavelength Tangent-Ring Metal–Insulator–Metal Waveguide", Sensors, 18, 1348 (2018). CrossRef